Trends in research on project-based science and technology teaching and learning at K–12 levels: a systematic review - Hasni, Abdelkrim; Bousadra, Fatima; Belletête, Vincent; Benabdallah, Ahmed; Nicole, Marie-Claude; Dumais, Nancy (Studies in Science Education, 2016)
Project-based teaching is nothing new; it originates from the work of authors like Dewey and Kilpatrick. Recent decades have seen renewed interest in this approach. In many countries, it is currently considered to be an innovative approach to science and technology (S&T) teaching. In this article, we present a systematic review of what recent scientific publications teach us about this approach: How is this approach identified in these publications? How is the use of this approach in school S&T justified? What are the main research questions covered by studies in the field? What do these studies on this approach teach us? To answer these questions, we have selected and analysed articles published, between 2000 and 2014, in journals that are specialised in school science and technology education and that are indexed in ERIC database. In the synthesis based on this analysis, we present: (a) the theoretical constructs used by the authors to refer to this approach and the features identified to define it; (b) the justifications for this approach; (c) the research questions covered by studies in the field; (d) the data collection and analysis methods used in these studies; and (e) the main findings. In addition to presenting a synthesis of current research in this field, we offer a critical discussion thereof with a focus on two aspects, namely the way PBSTL is conceptualised and the rigour of the research methods used to ensure the validity of findings.